Analisis Trend dan Faktor-faktor yang Memengaruhi Volume Penjualan Produk Benih Kubis Green Nova di PT. Tani Murni Indonesia - Baharsyah, Rifky; Prasetyo, Edy; Ekowati, Titik (Universitas Galuh, 2025)
PT. Tani Murni Indonesia is a company engaged in the production, research, breeding, and distribution of high-quality vegetable seeds in Indonesia. The company produces its own hybrid seeds through a Research and Development process, resulting in unique varieties with superior quality. This study aimed to analyze the sales trend of Green Nova cabbage seeds at PT. Tani Murni Indonesia and to examine the influence of selling price, production volume, promotional costs, transportation costs, and planting season on the sales volume of Green Nova cabbage seed products. The research was conducted from January 2025 to February 2025 using a case study method at PT. Tani Murni Indonesia. Primary data were collected through interviews using questionnaires, while secondary data were obtained through literature studies relevant to the research topic. The time series data used in this study covered a period of five years and included data on selling prices, production volumes, promotional costs, transportation costs, and planting seasons. The analytical methods employed in this research were trend analysis and multiple linear regression analysis. The results of the trend analysis, using linear trend analysis, showed a sales forecast of 66,804.366 packs over 24 months, from January 2025 to December 2026. The results of the multiple linear regression analysis indicated that selling price, production volume, transportation costs, and promotional costs had a significant effect on sales volume, while the dummy variable for planting season had no significant effect on sales volume.